Empirical study on the integrated management system in Algerian companies - Samiya Benyettou; Megnounif Abdellatif (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: The integrated management system concept has been installed recently in Algerian companies. A theoretical model is proposed which is based on a functional analysis of the systemic approach. This model is a cycle of seven requirements (organization context, leadership, planning, support, implementation of operational activities, performance evaluation and improvement), in addition to the inputs and outputs. The purpose of this article is to, empirically, investigate the current status of integrated management system and test its performance in Algerian Companies. Design/methodology/approach: In order to achieve this objective, a structured questionnaire survey is chosen in this study and sent to the 250 selected companies, only 115 of them have responded among them 65 have already implemented an integrated management system (IMS). These companies have different sizes and activities, and operate across the national territory in Algeria. This study employed both exploratory (EFA) and confirmatory (CFA) techniques in the factor analyses and also, in order to identify the relationships between the theoretical constructs, correlation and stepwise regression analyses were used. Findings: From the results, the research reflects the status of IMS in Algeria. The findings provide specific actions in order to help to clarify the understanding of the integration process within the Algerian companies which seems have some difficulties to implementing the IMS. Research limitations/implications: One of the major limitations of this study is the small simple size, which precludes generalization of the findings. This study provides a starting point for further research in developing countries. Originality/value: This paper offers first key insights into IMS implementation in Algeria. This will encourage many local organizations as well as some others in developed countries to adopt the proposed IMS model.
Keywords: 650; Algerian companies; CFA; EFA; integration; management system